2020
DOI: 10.3390/molecules25163618
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Studies on Graphene-Based Nanomaterials in Aquatic Organisms: Current Understanding

Abstract: Graphene and its oxide are nanomaterials considered currently to be very promising because of their great potential applications in various industries. The exceptional physiochemical properties of graphene, particularly thermal conductivity, electron mobility, high surface area, and mechanical strength, promise development of novel or enhanced technologies in industries. The diverse applications of graphene and graphene oxide (GO) include energy storage, sensors, generators, light processing, electronics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 113 publications
0
34
0
Order By: Relevance
“…As many other studies have indicated, various factors, such as concentration, surface structure, size and shape, can affect the cytotoxicity of graphene-based materials. 49,55,56 Animals were exposed to lateral spinal cord damage at T10 through compression. The treatment group received a sufficient amount of therapeutic nanocomposites (GO-PEG + GO-CS).…”
Section: Dls Results Inmentioning
confidence: 99%
“…As many other studies have indicated, various factors, such as concentration, surface structure, size and shape, can affect the cytotoxicity of graphene-based materials. 49,55,56 Animals were exposed to lateral spinal cord damage at T10 through compression. The treatment group received a sufficient amount of therapeutic nanocomposites (GO-PEG + GO-CS).…”
Section: Dls Results Inmentioning
confidence: 99%
“…Zebrafish have been previously used to study the impact of GRMs [38][39][40][41][42][43][44] and were exploited here to report that the degree of GO thermal reduction, which decreases the O/C ratio in the nanomaterials, induces diverse GRMs effects on the sensory-motor nervous system of vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Chung‐Der Hsiao et al assessed toxicity studies on graphene‐based nanomaterials in aquatic organisms. They showed that Reactive Oxygen Species (ROS) elevation, lipid peroxidation, nutrient/oxygen depletion, and inflammation have been most widely recognized mechanisms for graphene‐based nanomaterials toxicity in aquatic organisms, although the particular mechanism for their toxicity has not yet been established (Malhotra et al, 2020).…”
Section: Discussionmentioning
confidence: 99%